Annual Plan 2008-09 Draft Planning and Development Department Government of Jharkhand - Planning Commission (Planning Commission, 2008)
Jharkhand emerged as 28th State on the political map of India on 15 November 2000. Chotanagpur plateau and Santhal Paragna regions, once the part of Bihar, now form the State of Jharkhand. The State is covered by forest lands and hills varying from 300 to 1000 mtrs in altitude. The State has sizeable tribal population and rich in vegetation and mineral resources. Presently it has been organised into 24 districts. The State covers about 2.42% of the country's land area ( 79,710 Sq. Km) and about 2.62 % of the country's population (2.69 crores as per Census 2001).
Planning and Development Department Government of Jharkhand